2020
DOI: 10.3389/fbioe.2020.00791
|View full text |Cite
|
Sign up to set email alerts
|

Soft Matrix Combined With BMPR Inhibition Regulates Neurogenic Differentiation of Human Umbilical Cord Mesenchymal Stem Cells

Abstract: Stem cells constantly encounter as well as respond to a variety of signals in their microenvironment. Although the role of biochemical factors has always been emphasized, the significance of biophysical signals has not been studied until recently. Additionally, biophysical elements, like extracellular matrix (ECM) stiffness, can regulate functions of stem cells. In this study, we demonstrated that soft matrix with 1-10 kPa can induce neural differentiation of human umbilical cord mesenchymal stem cells (hUC-MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…37 In regard to neurogenic differentiation, soft matrix with 1-10 kPa favored neural differentiation of human umbilical cord mesenchymal stem cells. 35 Consistently, in our study, the average elastic moduli of 5% (wt/vol) GelMA hydrogels was 3.21 ± 0.54 kPa which was within the range of 1-10 kPa. Therefore, 5% (wt/vol) GelMA hydrogel was selected to be utilized in further experiments to provide a 3D microenvironment for neurogenic differentiation.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…37 In regard to neurogenic differentiation, soft matrix with 1-10 kPa favored neural differentiation of human umbilical cord mesenchymal stem cells. 35 Consistently, in our study, the average elastic moduli of 5% (wt/vol) GelMA hydrogels was 3.21 ± 0.54 kPa which was within the range of 1-10 kPa. Therefore, 5% (wt/vol) GelMA hydrogel was selected to be utilized in further experiments to provide a 3D microenvironment for neurogenic differentiation.…”
Section: Discussionsupporting
confidence: 90%
“…NSCs have been reported to display morphological changes in response to varying substrate stiffness, 33 with relatively softer substrata being more conducive for neuronal differentiation and maturation. 34,35 Thus, in this study, we fabricated 5%, 10%, and 15%…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies have shown that mesenchymal stem cells (MSCs), which are similar in origin to osteosarcoma cells, show different differentiation trends under different matrix stiffnesses. MSCs on soft substrates tend to neural and adipogenic differentiation, while MSCs on stiff substrates tended to cartilage and osteogenic differentiation (17,18,19,20). Based on the above evidence, we speculate that a similar phenomenon may also exist in osteosarcoma.…”
Section: Introductionmentioning
confidence: 59%
“…For example, culture on rigid surfaces can induce osteogenic and adipogenic differentiation [9,69,70]. Soft tissues and surfaces induce MSCs towards the myogenic and neurogenic lineages [71][72][73][74][75]. Thus the stiffness of a surface or microenvironment can influence the expression of markers and shape of MSCs both in vivo and in vitro ( Figure 3) [76][77][78].…”
Section: Sources and Niche Of Adult Mesenchymal Stem/stromal Cellsmentioning
confidence: 99%